Max is missing ([Canada] Trinity Pictures, 1995)
Max is forced to vacation in Peru with his historian dad and his new girlfriend. During a hike through some South American ruins, Max escapes from his dad's childish romantic behaviour to explore on his own. During his independence, a strange man give Max a priceless relic and explains he must not let it fall into the wrong hands. Max soon finds himself being followed by two suspicious men. therefore, Max seeks help from a local teenager to help him outsmart the follower. The two boys find themselves on an adventure of a lifetime when they discover they hold the power to a million dollar treasure.
The Sacred Valley -- Treasure Hunter -- Mountain Adventure -- Dangerous Game -- Stolen Bag -- Safe on shore -- New deal -- History lesson -- The Curandera -- Police station -- Held Captive -- A true friend -- The great Inca -- Ransom Plan -- Uprising -- End Credits.
Director of Photography, Blake T. Evans ; Production Designer, Robert de Vico ; Music by, Arthur Kempel
Toran Caudell, Victor Rojas, Matthew Sullivan, Alexandra Hedison, Rick Dean, Ramsay Ross, Iris Peynado, Charls Napier.
In English.
Keywords: Adventure films